Where I can't follow : a novel - Blooms, Ashley (Sourcebooks Landmark, 2022)
"Maren Walker dreams of finding her own little door. The doors have appeared to the people in her mountain town for as long as anyone can remember, though no one knows where they lead. Maren's mother was the last to go through, leaving nine-year-old Maren behind. Now living with her grandmother, Maren deals prescription medication to pay their bills and nurture her dream of becoming a nurse. When she faces the possibility of escaping her struggles or good, Maren must choose just what kind of future she wants to build. From critically acclaimed author Ashley Blooms, Where I Can't Follow explores the forces that hold people in place, and how they adapt, survive, and struggle to love a place that doesn't always love them back"--